Study on effect of variations of meta-kaolin addition on Self-Compacting parameter of High Strength Concrete - Wibowo, Wibowo; A, Mediyanto; Dharmawan, E A (International Journal of Integrated Engineering, 2018)
High strength self-compacting concrete (HSSCC) is one of the concrete innovations that have a high quality standard. This type of concrete has a high compressive strength and can compact without tools. Meta-kaolin (MK) is used in this research as an addition (admixture) to increase the quality of HSSCC and to meet criteria of SCC. Meta-kaolin (MK) is made from kaolin which a white powder is measuring 0.5 to 5 micron that then heated at 500– 900oC. Parameters that are studied in this research are setting time, workability, and the compressive strength of HSSCC. Final results of the research shows that the addition of MK decrease workability of HSSCC. Only MK addition at 5%, 7.5%, and 10% fulfils filling ability and passing ability parameter of SCC, otherwise the compressive strength increases linearly.